Alternative source of financing for start-up solar companies in Malaysia - Afroz, Rafia (2020)
In Malaysia, energy consumption by households grew by 6.9%. Meanwhile, energy supply rose 6.1% from 1991 to 2006. Thus, if energy consumption continues to increase in the future, the supply of energy will be lacking. The steady growth of electricity consumption in Malaysia is directly linked to CO2 emissions and climate change, which increases the annual temperature and temperature-related health problems. The use of PV solar energy may be an effective solution, but there are some barriers faced by Malaysian households, such as high prices, lack of physical and financial facilities, lack of awareness and social support. The objective of this study is to review the energy situation, barriers and challenges of solar energy in Malaysia. Lastly, this paper proposed an alternative source of financing for solar energy usage in Malaysia.